Formication with destruction of the nasal septum: A rare case report - Michele White; Dwayne Evans; Gary Frey; Cleverick CD Johnson; Ben F Warner (SAGE Open Medical Case Reports)
Delusions of parasitosis are known by several names, one of which is formication. It is an uncommon psychiatric disorder listed in the DSM V under the classification of delusional disorders. Patients experience an established, incorrect belief that they have an infection of living organisms such as parasites. There are two types of delusions of parasitosis, primary and secondary. In the primary form, the symptom is the delusion of a parasitic infection without secondary cause. The secondary form includes this symptom as well as additional psychiatric disorder, drug abuse, or medical illness. Patients often seek consultation with dental providers for dental pain with underlying medical conditions. This is a case report of a 35-year-old male with comorbid HIV and Hepatitis B disease, as reported by the patient, who sought care with a dental urgent care clinic with a chief complaint of dental pain and a presentation of collapse, atrophy, and ebbing of the nasal septum due to patient admitted formication. An accurate and complete medical was not obtainable from the patient who was subsequently lost to follow-up. Patient symptoms, clinical examination, and differential diagnosis rationale are presented. Further, information on cocaine and methamphetamine is also discussed. Followed by the conclusion that advocates for the usefulness of this case report for primary medical and dental providers. Recognition of concurrent medical and dental conditions will expedite collaborative care, patient referral, and treatment options that support best practices in patient care.